Model Optimasi dan Manajemen Risiko pada Saluran Distribusi Rantai Pasok Sayuran Dataran Tinggi Wilayah Sumatera - Yuviani Kusumawardhani; Muhammad Syamsun; Anggraini Sukmawati (MANAJEMEN IKM: Jurnal Manajemen Pengembangan Industri Kecil Menengah, 2015)
Agricultural sector, especially in highland vegetables are considered to have the potential and prospects to support diversification. It should have a comparative value advantage. Comparative advantages are obtained with supply chain management and risk management therefore needs a model of optimization. But often the common agricultural activities appear particularly at risk of supply chain distribution channel. Risk management is essential to minimize the risks and part of the supply chain management. The purpose of this study are (1) analyze how the supply chain flow in highland vegetable Agam District, West Sumatra and Karo District, North Sumatra, (2) knowing the model optimization and risk management in the vegetable supply chain distribution channels in Agam District, West Sumatra and Karo District Karo, North Sumatra, and (3) analyze how to minimize risk in the highland vegetable distribution channels in Agam District, West Sumatra and Karo District, North Sumatra. In analyzing the model optimization and risk management in the supply chain distribution channel highland vegetables in Agam District, West Sumatra and Karo District, North Sumatra used AHP (Analysis Hierarchy Process) and for risk minimization used the ISM (Intrepretive Structural Modeling). The results of the study will provide a model optimization and risk management in the supply chain distribution channel highland vegetables in order to have a comparative value.